Perkembangan Teater di Bali melalui Sosok Dramawan Abu Bakar - I Nyoman Darma Putra, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
A Western-style of theatre has developed in Bali since the turnof the twentieth century, but it has rarely attracted scholarlyattention. Studies on the performing arts in Bali have mainlyfocused on Balinese (traditional) dance and drama. This shouldcome as no surprise given that Balinese dance and dramahave developed as a broad and inseparable part of Balinesecustom and religious practice. Against this phenomena, thisarticle traces the development of Western-style theatre in Balithrough the artistic activities of the prominent playwright,performer and director, Abu Bakar. From the 1960s until thepresent, Abu Bakar has been an active promoter of Westernstyletheatre in Bali as well as in the main cities of Java andeven in Singapore. He has also has helped students and theatregroups around Bali to study and perform theatre. Initially, AbuBakar established his own theatre group, Poliklinik, which hascontinued to stage performances as well as collaborating withyoung people or student theatre study clubs. His extensiverecord of artistic activity has been recorded in newspaperreports and reviews and these form the main source ofdocumentation in this article. By examining qualitative datacollected from newspaper archives and interviews, includingwith Abu Bakar, this article proposes a contemporary historyof theatre or modern drama in Bali.
Keywords: Bali; theatre; modern performing arts; traditional performing arts; modern drama